Is the Modern State Compatible with Islam? - Zemoura, Nawal (Muslim Politics Review, 2024)
The Impossible State: Islam, Politics, and Modernity’s Moral Predicament. Wael B. Hallaq, New York: Columbia University Press, 2012. This book examines compatibility between the modern state and Islam. The author, Wael B. Hallaq, argues that the modern state, which are the result of the European enlightenment project, is incompatible with Islam because it lacks the moral and ethical standards sanctioned by Islam.